Monitoring Oxidation of Chlorinated Ethenes by Permanganate in Groundwater Using Stable Isotopes: Laboratory and Field Studies - Hunkeler, Daniel; Aravena, Ramon; Parker, B. L.; Cherry, J. A.; Diao, X. (My University, 2003)
Permanganate injection is increasingly applied for in situ destruction of chlorinated ethenes in groundwater. This laboratory and field study demonstrates the roles that carbon isotope analysis can play in the assessment of oxidation of trichloroethene (TCE) by permanganate. In laboratory experiments a strong carbon isotope fractionation was observed during oxidation of TCE with similar isotopic enrichment factors (−25.1 to −26.8 ‰) for initial KMnO4 concentrations between 67 and 1250 mg/L. At the field site, a single permanganate injection episode was conducted in a sandy aquifer contaminated with TCE as dense nonaqueous liquid (DNAPL). After injection, enriched δ13C values of up to +204% and elevated Cl- concentrations were observed at distances of up to 4 m from the injection point. Farther away, the Cl- increased without any change in δ13C of TCE suggesting that Cl- was not produced locally but migrated to the sampling point. Except for the closest sampling location to the injection point, the δ13C rebounded to the initial δ13C again, likely due to dissolution of DNAPL. Isotope mass balance calculations made it possible to identify zones where TCE oxidation continued to occur during the rebound phase. The study indicates that δ13C values can be used to assess the dynamics between TCE oxidation and dissolution and to locate zones of oxidation of chlorinated ethenes that cannot be identified from the Cl- distribution alone.